Eksperimentasi Pembelajaran RealistikditinjaudariAktivitas Belajar SiswapadaMateri Segiempat - Azizah, Dewi (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The purpose of the research was to describe the differences betweenRealisticMathematicsEducation and Mechanisticlearning approachin mathematics achievementviewed from students’ activity. The research was a quasi experimental. The population of the research was all the seventh grade students of junior high schoolin Pekalongan regency. The instruments used to collect the data were achievment on quadrilateral topic and questionnare of the students activity in learning mathematics. To analyze the data, the researcher used anova (analysis of variances) with unbalanced cells. It was concluded that Realistic MathematicsEducation gave a betterresult than Mechanistic learning approachon quadrilateraltopic and the students mathematics achievement for the students that high activity was better than those who had a moderate and low activity, whereas the studentsmathematicsachievement that had a moderate activity was equivalence to the students who had a low activity.Keywords: Realistic Mathematics Education, quadrilateral, learning activity